Penerapan SNI 2847:2019 dalam Evaluasi Kapasitas Lentur dan Geser Balok Beton Bertulang dengan Data Aktual - Hafidz Maulana; Imam Mustofa (Universitas Batanghari Jambi, 2026)
Reinforced concrete beams are primary structural elements responsible for transferring gravity loads and play a crucial role in maintaining the stability and safety of building structures. In construction practice, variations in concrete strength, reinforcement ratios, and execution irregularities often cause the flexural and shear behavior of beams to differ from design assumptions, making capacity evaluation based on actual section data necessary. This study aims to evaluate the flexural and shear capacity of reinforced concrete beams and to assess the level of capacity utilization under design gravity loads. The research method employs an analytical approachc approach using section geometry, material properties, reinforcement configuration, and gravity loading obtained from design documents. Internal forces are calculated using static equations for simply supported beams, while flexural and shear capacities are determined in accordance with the provisions of SNI 2847:2019 and the load combinations specified in SNI 1727:2020. The results indicate that the factored bending moment of 232.37 kNm and the shear force of 84.88 kN remain below the design capacities φMn of 452.81 kNm and φVn of 206.86 kN, resulting in utilization ratios of 0.51 and 0.41, respectively. The provided flexural and shear reinforcement also satisfies strength and detailing requirements. It is recommended that evaluations based on actual section data be consistently applied to improve design reliability and quality control in reinforced concrete beam construction.